Mempertanyakan Gelar Abraham sebagai Bapa Orang Beriman Setelah Peristiwa di Mesir - Kejadian 12:10-20 - Seri Damarwanti (SANCTUM DOMINE: JURNAL TEOLOGI, 2019)
The title of Abraham as "father of the faithful" written in the Bible contains various meanings related to the nature of the concept of salvation. This title breaks down some of the stories and history behind it in Genesis 12:10-20 which contrasts with the awarding of the title. A comprehensive in-depth study is needed from various points of view to find out the basis and purpose of God's choice fell on Abraham. Paul's perspective in the Romans and James's perspective in the James become the chosen reference for exploring the facts behind the title. The author's view is presented as a conclusion to the writings of Paul and James, and is understood as God's sovereign perspective on the salvation of mankind.